History and Culture of the Gado Dayak Community As a Source of Environmental-Based History Learning - Agus Dediansyah; Basuki Wibowo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2022)
The people of West Kalimantan make nature a buffer for the economy. The Gado Dayak community is one of the people who make nature be it forests, rivers, and fields as the fulfillment of life. Friendly nature management needs to be passed on to the younger generation through environmental-based history learning. This study aims to determine (1) the history of the Daya Gado Community in Landak Regency (2) Culture of the Gado Dayak Community (3) The historical potential of the Gado Dayak as a source of environmental-based history learning. The research method used is historical research which includes heuristics, source criticism, interpretation, and historiography. The results of the study explain that the history of the Dayak Gado community cannot be separated from the process of community migration due to natural disasters which finally made the Dayak Gado community separated into 3 Ketemenggungan. The shift of the Gado people from their initial place of refuge due to natural disasters made them separated but they still maintain the traditions of their ancestral heritage in the form of farming, hunting and finally the arrival of missionaries. The Capuchins who teach rubber plantations and the Chinese who teach the clearing of rice fields have changed the culture of cultivators to farmers to meet the rice needs of gold miners in the Monterado and Mandor areas. The history of the Gado Dayak community can be used as environmental-based history learning. The life of the Gado Dayak community can be used as a learning resource that is developed in junior high school through social studies subjects and high school through history subjects. The application of integrated learning models, such as in social studies subjects, can increase students' knowledge of environmental conditions so that they can be ready if something unexpected happens, such as a natural disaster.